IMPLEMENTASI PENYELESAIAN SENGKETA PAJAK PADA KANTOR WILAYAH DIREKTORAT JENDERAL PAJAK JAKARTA TIMUR - Ghifari, Muhammad; Rahmadi, Heksawan (Institut Ilmu Sosial dan Manajemen STIAMI, 2025)
The phenomenon in this study concerned the condition of tax dispute resolution, which was abundant and time-consuming. Taxpayers' considerations in responding to decisions issued by the Directorate General of Taxes relate to the legal remedies provided under Article 25 and Article 27 of the General Provisions and Tax Procedures Law. The purpose of this study was to examine how the implementation of tax dispute resolution at the Regional Office of the Directorate General of Taxes (DJP) East Jakarta was carried out, as well as the inhibiting factors and solutions in implementing tax dispute resolution.This research employed a descriptive study with a qualitative approach. The analysis method used was qualitative data analysis. The research location was the Regional Office of DJP East Jakarta. The results of this study indicated that the implementation strategy carried out by the Regional Office of DJP East Jakarta has been quite successful, as seen from the key performance indicators in 2024, which exceeded the target, achieving 88.43% compared to the target of 79%.